Physical and chemical oceanography during SONNE cruise SO277 from towed Video-CTD02, off Malta - Mark Schmidt (PANGAEA, 2025)
Data set presents water column and bottom water oceanographic parameters recorded with a video-guided Water Sampler Rosette/CTD system during SO277 cruise off Malta (Berndt et al., 2021). The data set of VCTD02 was recorded on August 26th, 2020 and combines Seabird-CTD data with methane and CO2-sensor data and ship extquotesingles navigation data (SeaPath, Kongsberg SP 320-5+). Data were recorded to localize fluid seepage at the seafloor east of Malta and Gozo.